Experimental Investigation and Load Capacity of Slender Cold-Formed Lipped Channel Sections with Holes in Compression - Xingyou Yao (Advances in Civil Engineering)
The use of cold-formed steel (CFS) channels with circular or rectangular web holes is becoming increasingly popular in building structures. However, such holes can result in sections becoming more susceptible to buckle and display lower load-carrying capacities. This paper presents a total of 42 axial compression tests of CFS lipped channel slender columns with and without circular and rectangular web holes, including different hole sizes and cross sections. The test results show that the axial members with a small ratio of width to thickness were governed by global buckling, while the members with a large ratio of width to thickness were controlled by the interaction of local, distortional, and global buckling. The axial strength decreased maximum by 20.48% and 22.98% for the member with circular holes and rectangular holes, compared to a member without a web hole. Then, a nonlinear elastoplastic finite element model (FEM) was developed, and the analysis results showed good agreement with the test results. The validated FE model was used to conduct a parametric study involving 36 FEMs to investigate the effects of column slenderness, dimension of the hole, and the number of holes on the axial strength of such channels. Furthermore, the formulas to predict the global buckling coefficient and the effective area were modified for such sections with holes by using the verified FEM. Finally, the tests and parametric study results were compared against the design strengths calculated in accordance with the developed method. The comparison results show that the proposed design method closely predicts the axial capacity of CFS channels with circular or rectangular web holes.